Study on the Enhancement of Malaysian ICU Centre and Introduction of STAR Performance - Rosly C.Z.; Jamaludin U.K.; Khalid K.; Suhaimi F.; Abdul Razak N.N.; Mat Nor M.B.; Md Ralib A. (Springer Science and Business Media Deutschland GmbH, 2023)
Blood; Glucose; Insulin; Intensive care units; Patient treatment; Stars; Stochastic systems; Hyperglycaemia; Hypoglycaemia; Intensive insulin therapies; Performance; Stochastic targeted; Stochastics; Stress induced hyperglycemia; Stress-induced; MATLAB